مفهوم المقدّس والمدنس عند ميرسيا إلياد : دراسة نقدية فقييمية من وجهة نظر إسلامية - سلام، عبد الناصر سلطان محسن (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
The term 'sacred' in the study of religions appeared at the beginning of the last century Western scholars studied primitive religions in the world and combined it with the term of 'profane' in an ambivalent or a deterministic relationship. Mircea Eliade was one of those scholars who used the terms in in a different ways from most of his predecessors who set off on their studies of them from the reductionist approaches to religion. Eliade studied the 'sacred' in its religious sense as a revelation or a fundamental and common source to all religions and beliefs, proceeding from human existence and his understanding of the being as a central unit of these religions and beliefs. This study is an analysis of what was written by Eliade about the 'sacred' and the 'profane' from his understanding of the initial and ancient religions, from which are formulated specific archetypes that are known to him in all religions and beliefs, and explained on its basis in human behaviour in general and religious behaviour in particular. The study identifies, through analysis of the nature of the 'sacred' and the 'profane' by Eliade, the three hierophanies of the sacred: the 'sacred symbol, the sacred time, and the sacred place. The study reveals Eliade's understanding of religion which he pictures in the cosmic religious doctrine that he alleges as the truth of all religions and beliefs. The study of Eliade's concept of the 'sacred' and the 'profane' of Eliade raises the issue of the 'sacred' and the 'profane' in Islam, by comparison and criticism of Eliade's concept, through defining the sacred and the profane in Islam and their relation to Muslims' cosmic concept.